Unveiling challenges and strategizing solutions for sustainable agri-entrepreneurship development - Kademani, Sujay; Nain, Manjeet Singh; Singh, Rashmi; Kumar, Shiv; Parsad, Rajender; Sharma, Dinesh Kumar; Roy, Surjya Kanta; Karjigi, Krishna D.; Prabhakar, Itigi; Mahapatra, Ankit; Patil, Manjuprakash (Frontiers in Sustainable Food Systems, 2024)
The increasing emphasis on fostering agri-entrepreneurship in emerging economies is based on the understanding that it holds the potential to drive economic growth and sustainable development. Its impact transcends mere financial indicators, influencing facets such as innovation, job creation, and societal empowerment. This perspective is also relevant in the Indian context, where organizations promoting agri-entrepreneurship often encounter challenges. This study was carried out to identify the constraints faced by various stakeholders involved in providing and accessing entrepreneurial support, also strategizing solutions for the identified bottlenecks. Data was gathered through structured interviews involving about two hundred agri-entrepreneurs and forty-three extension professionals in selected states. Constraints as well as strategies in the promotion of agri-entrepreneurship were systematically categorized into four dimensions viz. administrative, financial, technical, and socio-cultural which were further ranked through Garett’s ranking method and Analytical Hierarchy Process. Financial and administrative constraints, including lack of priority lending, favouritism, and delays in fund release, emerged as significant hurdles for sustainable entrepreneurship development, other constraints among technical and socio-cultural domains include lack of prototype testing facility and orientation towards conventional ventures, respectively. Experts suggested strategies like post programme funding support, timely disbursement of seed funding and transparency in pitch evaluation for mitigating the challenges. The overall consistency ratio of AHP matrix indicates a high level of agreement in suggestions among experts.Incorporating the suggestions through policy changes is expected to promote a sustainable food value chain thereby promoting sustainable agri-entrepreneurship.